THE SINKING OF SOVEREIGNTY AND SOVEREIGN RIGHTS? MITIGATING THE IMPACTS OF CLIMATE CHANGE TO MARITIME JURISDICTION AND A PROPOSAL FOR SOLUTIONS - Arsana, I Made Andi (UI Scholars Hub, 2013)
While some still debate whether or not climate change is a reality, one of its impacts, sea level rise, is factual. The cause and the rate of sea level rise might have been inconclusive but its impacts have been clearly felt. Sea level rise can also change the legal status of insular features (small islands/rocks and low tide elevation) that will also affect their capacity in making maritime claim. For an archipelagic State like Indonesia, small outer islands/rocks or low-tide elevation are important for location of basepoints forming the entire system of archipelagic baselines. This paper investigates the impact of sea level rise to the change of baselines and maritime limits a coastal state may claim. On the other hand, there is a need to have fixed maritime limits for better management and to balance rights and duties of coastal to the ocean. This paper provides options on how Indonesia as a coastal and archipelagic State can fix their baselines and or maritime limits in the face of coastal instability due to sea level rise as a consequence of climate change.